Pembuatan NIB dan Sertifikasi Halal: Penguatan Strategi Pengembangan UMKM di Desa Duwet dan Desa Watesalit - Nuruzzuhrotil 'Ula, Zava; Mutiara, Dwi; Zulfa, Amalina (Social Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
Legality is very important for a business. This is in line with the new policy issued by the government to have complete and legal permits. The existence of licensing places responsibility on business actors to ensure that the quality of the products produced is maintained responsibly. The legality that will be the output in this service activity is the Business Identification Number (NIB) and Halal Certification. The purpose of this service is so that business actors can understand the importance of business legality and have business legality for small and medium business actors to support their business development, business actors know how to obtain business permits, and business actors have business legality, in this case in the form of NIB and Halal Certification. The method used in this service activity is divided into two stages, namely: 1. Education and survey stage, in this stage the team provides education by explaining to business actors about NIB, the advantages of having NIB and procedures for registering NIB through OSS. Then proceed with a survey to collect data 2. Manufacturing stage, the NIB creation stage is carried out independently by the service implementation team, after the NIB is issued, it is continued with the halal certification registration process. The result of this service activity is that business actors know the importance of business legality and the issuance of Business Identification Numbers (NIB) and halal certification for business actors in Duwet Village and Watesalit Village.